Instructional Design Framework for EFL Students in Cultivating Project-Based Language Learning - Atika Kumala Dewi; Nunung Suryati, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Project-Based Language Learning (PBLL) offers a transformative learning experience to involve language learners in real-world issues of the target language achieved by creating products that serve a genuine purpose. Therefore, instructional design framework of PBLL for English as A Foreign Language (EFL) students in higher education is crucial. In addition, they must also acknowledge PBLL as it is a mandatory based on OECD (2016). As a results, this study aims to investigate the implementation of PBLL for EFL students for the instructional design framework of PBLL use enhancement. To accomplish this aim, a systematic literature review (SLR) was employed by extracting from the SCOPUS database as publications on international practices. In total, 24 documents from the last five years (2018–2023) were included by PRISMA Analysis for the data selection, Mendeley reference manager for the data extraction and VosViewer software application for the data analysis. The findings indicate that PBLL comprises Discovery Learning (DL), Cooperative Learning (CL), and Reflective Learning (RL). It includes the benefits of training, critical thinking, creativity, collaboration (in groups), and student motivation in learning, which are attributes that are shared by several of the learning models that are applied in ELF learning. Specifically, ELF learning utilizes cooperative learning, cooperative problem solving, cooperative problem solving in groups, and cooperative problem solving individually. Additional research is required to effectively develop learning designs based on this framework. It contributes to the existing literature by providing an understanding of the evolution of PBLL research topics in EFL.